Influence of pH and temperature on soluble substrate generation with primary sludge fermentation - Cokgor, Emine Ubay; Oktay, Seda; Tas, Didem Okutman; Zengin, Gulsum Emel; Orhon, Derin (Elsevier BV, 2009)
The study was undertaken to evaluate the effect of pH and temperature control on the generation of soluble fermentation products from primary sludge. The effect was tested by running parallel experiments under pH and temperature controlled and uncontrolled conditions. In fermentation experiments conducted at 20 degrees C without pH control, the average soluble COD release was 14 mg per liter of wastewater treated, representing a potential increase of 5% in the biodegradable COD content of the primary sedimentation effluent. The corresponding average VFA generation was 9.2mg COD l(-1). The nutrient release was practically negligible and stayed at 0.4 mg l(-1) for nitrogen and 0.1mg l(-1) for phosphorus. Acetic acid accounted more than 45% of the generated VFA in all experimental runs. The acetic acid content of the VFA decreased with increasing initial VSS concentrations and higher pH levels. VFA generation by fermentation was significantly affected with temperature and pH control. Temperature change between 10 and 24 degrees C induced a five-fold increase in VFA generation, from 610 mg l(-1) at 10 degrees C to 2950 mg l(-1) at 24 degrees C.
Keywords: Sewage; Cell Culture Techniques; Temperature; Hydrogen-Ion Concentration; Fatty Acids, Volatile; Models, Biological; Oxygen; Bioreactors; Solubility; Fermentation; Computer Simulation